Honeggeriella complexa gen. et sp. nov., a heteromerous lichen from the Lower Cretaceous of Vancouver Island (British Columbia, Canada)1. Issue 2 (1st February 2013) - Matsunaga, Kelly K. S.; Stockey, Ruth A.; Tomescu, Alexandru M. F.
Abstract : Premise of the study: Colonists of even the most inhospitable environments, lichens are present in all terrestrial ecosystems. Because of their ecological versatility and ubiquity, they have been considered excellent candidates for early colonizers of terrestrial environments. Despite such predictions, good preservation potential, and the extant diversity of lichenized fungi, the fossil record of lichen associations is sparse. Unequivocal lichen fossils are rare due, in part, to difficulties in ascertaining the presence of both symbionts and in characterizing their interactions. This study describes an exceptionally well‐preserved heteromerous lichen from the Lower Cretaceous of Vancouver Island. Methods: The fossil occurs in a marine carbonate concretion collected from the Apple Bay locality on Vancouver Island, British Columbia, and was prepared for light microscopy and SEM using the cellulose acetate peel technique. Key results: The lichen, Honeggeriella complexa gen. et sp. nov., is formed by an ascomycete mycobiont and a chlorophyte photobiont, and exhibits heteromerous thallus organization. This is paired with a mycobiont‐photobiont interface characterized by intracellular haustoria, previously not documented in the fossil record. Conclusions: Honeggeriella adds a lichen component to one of the richest and best characterized Early Cretaceous floras and provides a significant addition to the sparse fossil record of lichens. As a heteromerous chlorolichen, it bridges the >350 million‐year gap between previously documented Early Devonian and Eocene occurrences.